Standarisasi Indeks Eksposur untuk Memenuhi Kriteria Anatomi dan Aspek Teknis pada Radiografi Thorax Pediatrik - Mukhammad Lutfan Nurrokhim; Dwi Rochmayanti; Ari Budiono (Jurnal Imejing Diagnostik (JImeD), 2021)
Background: Computed Radiography has an exposure index that used as an exposure indicator. But on radiographic examination, exposure index value  sometimes ignored, and in  the preliminary survey of pediatric chest examination resulting a large exposure index range. The aim of this study is to know the profile of exposure index value and the setting of the exposure factors, the assessment of anatomy criteria and technical aspect, and the right exposure factors such as kV and mAs on pediatric chest examination.Methods: The type of this research is descriptive quantitative. The research was done by collecting data related to pediatric chest radiograph (≤ 2 years) the value of exposure index was recorded, then the radiograph was assessed using questionnaires that filled by one respondent who is a radiologist. The data was analyzed by displaying the data of exposure index and anatomy criteria from questionnaires into the table form, and then conducted a descriptive analysis to be drawn conclusions.Results: The results showed the profile of exposure index value and the setting of the exposure factor  has a fairly large exposure index range of 1084 – 2175, using 40 kV and 10 mAs and the collimation still often exceeds the object. Then for the assessment of the thorax anatomical criteria and the technical aspect overall was “Good Enough”, and the right exposure factors, that is: at 6 and 7 cm chest thickness was using 60 kV and 1,6 mAs; at 11 cm chest thickness was using 60 kV and 2 mAs, FFD 100 cm, and the setting of collimation as wide as object, the exposure index generated in the normal range that is 1251 – 1382.Conclusion: The right exposure factors on pediatric chest examination, that is: at 6 and 7 cm chest thickness was using 60 kV and 1,6 mAs; at 11 cm chest thickness was using 60 kV and 2 mAs, FFD 100 cm, and the setting of collimation as wide as object.